Hubungan Dukungan Keluarga dengan Kepatuhan Diet pada Penderita Hipertensi di Wilayah Kerja Puskesmas Gondangrejo Kabupaten Karanganyar - Anifah Nur Annisa; Dewi Kartika Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: The World Healt Organization (WHO) has determined that in 2022 there will be approximately 972 million people with hypertension worldwide. The incidence of hypertension tends to increase due to the lack of public knowledge about hypertension. Family support may improve dietary adherence in hypertensive patients. Support provided is form of emotional support, appreciation, informational, instrumental. Dietary adherence of hypertensive patients important determining the stability and normal value of blood pressure for the change from non-compliant behavior to compliant behavior. Objective: To analyze the relationship between family support and hypertensive dietary adherence in hypertensive patients in the Working Area of Gondangrejo Health Center, Karanganyar Regency. Methods: This study used quantitative method with zero observational analysis, sampling using the Qouta Sampling technique with sample of 91 respondents. Data analysis using Chi-square. Results: The statistical test research obtained p value of 0.183 > 0.05 so that there was no relationship between family support and dietary adherence in hypertensive patients in the working area of Gondangrejo Health Center, Karanganyar Regency. Conclusion: There is no relationship between family support and dietary adherence in hypertensive patients in the working area of the Gondangrejo Health Center, Karanganyar Regency.